2014
DOI: 10.1002/ams2.74
|View full text |Cite
|
Sign up to set email alerts
|

A simple predictive formula for the blood requirement in patients with high‐energy blunt injuries transferred within one hour post‐trauma

Abstract: Aims: To recognize patients who require massive transfusion at the early stage of blunt trauma, we retrospectively investigated patients with high-energy blunt injuries transferred within 1 h post-trauma. Methods:Between August 2007 and July 2011, 233 trauma patients were: (i) injured by a high-energy blunt mechanism with Injury Severity Score ≥9; (ii) not dead on arrival; (iii) older than 9 years; and (iv) at our center within 1 h after injury. The findings for 113 of those patients were analyzed, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The prediction of anemia using IVC diameter may be a potential outcome for future study. Three retrospective studies reported a massive transfusion requirement as a primary outcome [ 32 , 33 , 34 ]. Akasaki et al reported that a flat IVC with a T/AP ratio ≥ 3 was a significant risk factor for massive transfusion in a multivariable logistic regression [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prediction of anemia using IVC diameter may be a potential outcome for future study. Three retrospective studies reported a massive transfusion requirement as a primary outcome [ 32 , 33 , 34 ]. Akasaki et al reported that a flat IVC with a T/AP ratio ≥ 3 was a significant risk factor for massive transfusion in a multivariable logistic regression [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three retrospective studies reported a massive transfusion requirement as a primary outcome [ 32 , 33 , 34 ]. Akasaki et al reported that a flat IVC with a T/AP ratio ≥ 3 was a significant risk factor for massive transfusion in a multivariable logistic regression [ 32 ]. Chien et al reported that IVC volume was significantly related to massive transfusion in a multivariable logistic regression [ 33 ].…”
Section: Discussionmentioning
confidence: 99%